Pendidikan Berwawasan EkologI Realisasi Nilai-Nilai Ekologis dalam Kurikulum Pendidikan Agama Islam - Jatmiko, Agus (Universitas Islam Negeri Raden Intan Lampung, 2016)
This research aims to express the realization of ecological values in Islamic Education Curriculum in Elementary and High School. The problem which is looked for answer is, “How is the realization of ecological values in Islamic Education Curriculum in Elementary and High School?” This is qualitative research and data sources cover the books of Islamic Education Curriculum, its textbooks, and some books related to ecology. The data collected by bibliography study (library research), and later examined with the content analysis technique. Its result indicates that the ecological values in Islamic Education Curriculum in the school as whole are not realized explicitly, thought there are two (0, 42%) themes of environment, but its proportion is not adequate. Implicitly there are ten (2,11%) themes which can be developed in order to internalize ecology values.